Determinants And Consequences Of Rural-Urban Migration In Iran - -, Mohammad Ali Molaei (2008)
From the neoclassical view, rural-urban migration is positive and a necessary concomitant to development. But currently, migration is viewed as a negative factor by many development analysis. From the macro point of view, this study attempts to identify the relationship between macroeconomic variables such as income differentials, degree of development, and government expenditure on the one hand, and rural-urban migration on the other hand.